Pharmacokinetic Analysis of Epithelial/Endothelial Cell Barriers in Microfluidic Bilayer Devices with an Air–Liquid Interface - Timothy S. Frost; Linan Jiang; Yitshak Zohar (Micromachines, 2020)
As the range of applications of organs-on-chips is broadening, the evaluation of aerosol-based therapies using a lung-on-a-chip model has become an attractive approach. Inhalation therapies are not only minimally invasive but also provide optimal pharmacokinetic conditions for drug absorption. As drug development evolves, it is likely that better screening through use of organs-on-chips can significantly save time and cost. In this work, bio-aerosols of various compounds including insulin were generated using a jet nebulizer. The aerosol flows were driven through microfluidic bilayer devices establishing an air–liquid interface to mimic the blood–air barrier in human small airways. The aerosol flow in the microfluidic devices has been characterized and adjusted to closely match physiological values. The permeability of several compounds, including paracellular and transcellular biomarkers, across epithelial/endothelial cell barriers was measured. Concentration–time plots were established in microfluidic devices with and without cells; the curves were then utilized to extract standard pharmacokinetic parameters such as the area under the curve, maximum concentration, and time to maximum concentration. The cell barrier significantly affected the measured pharmacokinetic parameters, as compound absorption through the barrier decreases with its increasing molecular size. Aerosolizing insulin can lead to the formation of fibrils, prior to its entry to the microfluidic device, with a substantially larger apparent molecular size effectively blocking its paracellular transport. The results demonstrate the advantage of using lung-on-a-chip for drug discovery with applications such as development of novel inhaled therapies.